PENGARUH KONTEN LGBTQ+ TERHADAP SIKAP FOLLOWERS (STUDI KASUS PADA AKUN INSTAGRAM @TAULEBIH.ID) - Riskha Fitriana Utami (2023)
Various social media have emerged and often social media is used as a platform for users to freely recreate and express their aspirations. "Instagram is one of the many social media used and the most popular in Indonesia. Thanks to the support of various international communities for the legalization of LGBTQ+ rights, a contested human right, almost every day a lot of content on Instagram contains the circulation of information and activities of the LGBTQ+ community. One of them is the Instagram account @taulebih.id which often provides information about LGBTQ+ to provide more information about the LGBTQ+ community in the view of Islam. This study aims to examine the attitude of followers of the @taulebih.id Instagram account towards LGBTQ+ content on the @taulebih.id Instagram account because the @taulebih.id Instagram account is the only account that discusses Islamic-based sexual education and disseminates information about LGBTQ+. This research uses quantitative research methods with an explanatory approach. The theory used is information integration theory by Martin Fishbein which states that all information has latent power and can influence individuals to have certain attitudes. The data collection process uses a survey method in the form of a Google Form type questionnaire by distributing it via Direct Message (DM) on Instagram with a total of 100 respondents. The results of hypothesis testing using the t test show that the influence of @taulebih.id LGBTQ+ content with the dimensions of valence and weight has a significant effect on the attitude of followers. The results obtained Ha is accepted and Ho is rejected, which means that there is a significant influence on the attitude of followers or followers. This can be proven from the results of the data t count 14.789 which is greater than t table, namely 1.292 so that it can be concluded that the hypothesis is accepted.